Topical olive oil and narrow band ultraviolet-B trial for segmental vitiligo among adult Sudanese patients in Khartoum state, Sudan 2018 - Ali, Loai Gaffer Ahmed; A. Fadul, Al Taieb Mohammed; M. Taha, Mohammed Abdullah (International Journal of Research in Dermatology, 2019)
Background: Adult segmental vitiligo treated by narrow band ultraviolet B (NB-UVB) showed delayed repigmentation. This study is being undertaken to determine the efficacy of topical olive oil addition before (NB-UVB) sessions for vitiligo patients (pts). Methods: Randomized controlled trial (RCT) enrolled ten volunteers suffering segmental vitiligo on both upper limbs, all patients left limb was tested by topical olive oil before each NB-UVB session and twice daily in session free days for a total of 20 sessions (46 days), the right upper limb was the control (only NB-UVB), each site response was assessed based on time of appearance of erythema and repigmentation. Statistical analysis was done by the Chi-square test. Results: All patients were ten, seven were female (70%), three males (30%) of middle age group, university graduates live in Khartoum state. Their left upper limbs showed erythema in <3 sessions in five pts (50%) and three-five sessions in (50%), repigmentation started in <3 sessions in one patient (10%) and three-four sessions in five pt. (50%) and >5 sessions for four pts (40%), pattern of repigmentation was marginal in eight pts (80%), mixed in two pts (20%). Their right upper limbs showed erythema in three-four sessions in two pts (20%) and eight pts (80%) needed five sessions, repigmentation started after five sessions in all patients (100%), pattern of repigmentation was follicular in one pts (10%), marginal in five pts (50%), mixed in four pts (40%). Conclusions: Addition of topical olive oil to NB-UVB for segmental vitiligo patients showed earlier occurrence of repigmentation and better pigmentation pattern.